The Importance of Buddhism to Heal Trauma in Pahadi’s “The Tears of Terror” - Pokharel, Badri Prasad (Interdisciplinary Journal of Management and Social Sciences, 2023)
This article has tried to analyze Kishor Pahadi’s “The Tears of Terror” by applying Buddhism and its principal assets which would help the victims relieve from the pain and suffering or trauma they have got during the ten-year long Maoist insurgency. People during the decade-long conflict were badly inflicted by the fatal consequences from which they could hardly get over. Different measures were taken to help them get over, however, following some meditative aspects of Buddhism, one can get relief from the mental shock which has been imprinted in mind for a long time. This article is not talking about leaving home and going to the monasteries, rather it highlights some meditative aspects of Buddhism which can relieve the victims who is/are narrated in this story.